Analisis Implementasi Islamic Corporate Governance Pada Lembaga Keuangan Mikro Syariah Berbasis Pesantren - Sopia Laila Nugraha; Hikmah Endraswati (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2022)
The purpose of this study was to determine and analyze the implementation of Islamic Corporate Governance in Islamic microfinance institutions boarding school-based namely a study at BWM Almuna Berkah Mandiri Yogyakarta in 2020. This study used a qualitative descriptive approach with Miles and Huberman analysis techniques. Data were collected through observation, interviews, and documentation. This study looks at Islamic Corporate Governance (ICG) on sharia compliance with the representation of ICG principles on the leadership of Rasulullah SAW (shiddiq, amanah, tabligh, fathanah), fair and Shariah Compliance. The results of this study indicate that the implementation of Islamic corporate governance at the Islamic Microfinance Institution of the Micro Waqf Bank (LKMS BWM) Almuna Berkah Mandiri Yogyakarta in 2020 has not been implemented as a whole. When viewed using six indicators of Islamic corporate governance, LKMS BWM Almuna Berkah Mandiri has implemented ICG on the indicators of trust (trustworthiness/accountability), tabligh (delivering truth/responsibility), and fairness (fairness). LKMS BWM Almuna has not fully implemented ICG on indicators of shiddiq, fathanah, and shariah compliance in institutional governance, namely in delivering information to stakeholders, in terms of work experience (educational level) and HR expertise as well as auditing as needed in BWM LKMS governance.